The effect of volume equated 1- versus 2-day formats of Nordic hamstring exercise training on fitness in youth soccer players: A randomised controlled trial - Moran, Jason; Vali, Norodin; Drury, Ben; Hammami, Raouf; Tallent, Jamie; Chaabene, Helmi; Ramirez-Campillo, Rodrigo (PLOS ONE, 2022)
Purpose This randomised controlled trial examined the effect of an 8-week volume-equated programme of Nordic hamstring exercise (NHE) training, executed at frequencies of 1- or 2-days per week, on fitness (10 m and 40 m sprint, ‘505’ change of direction [COD] and standing long jump [SLJ]) in male youth soccer players (mean age: 16.4 ± 0.81 years). Method Players were divided into an experimental group (n = 16) which was further subdivided into 1-day (n = 8) and 2-day (n = 8) per week training groups and a control group (n = 8). Results There were significant group-by-time interactions for 10-m sprint (p<0.001, η2 = 0.120, d = 2.05 [0.57 to 3.53]), 40-m sprint (p = 0.001, η2 = 0.041, d = 1.09 [-0.23 to 2.4]) and COD (p = 0.002, η2 = 0.063, d = 1.25 [-0.09 to 2.59). The experimental group demonstrated a ‘very large’ effect size (d = 3.02 [1.5 to 4.54]) in 10-m sprint, and ‘large’ effect sizes in 40-m sprint (d = 1.94 [0.98 to 2.90]) and COD (d = 1.84 [0.85 to 2.83). The control group showed no significant changes. There were no significant differences between the 1-day and 2-day training groups. In three of the four tests (40 m, COD, SLJ) the 2-day group demonstrated larger effect sizes. Ratings of perceived exertion (RPE) were significantly lower in the 2-day group (p<0.001, 3.46 [1.83 to 5.04). Conclusion The NHE increases fitness in youth soccer players and there may be advantages to spreading training over two days instead of one.